2018
DOI: 10.1186/s40249-018-0403-x
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for prediction of Mycobacterium tuberculosis positivity detected with bronchoalveolar lavage fluid

Abstract: BackgroundThe diagnosis of active pulmonary tuberculosis (TB) remains a challenge in clinic, especially for sputum negative pulmonary TB. Bronchoalveolar lavage fluid (BALF) has higher sensitivity than sputum for detection of Mycobacterium tuberculosis (Mtb). However, bronchoscopy is invasive and costly, and not suitable for all patients. In order to make TB patients get more benefit from BALF for diagnosis, we explore which indicator might be used to optimize the choice of bronchoscopy.MethodsA total of 1539 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…In our study, samples sequenced from BALF had a higher reference genome coverage as compared with those obtained from sputum, and this was correlated to the number of lineage-specific reads in BALF samples that was significantly more than in sputum samples, and the drug resistance was mostly discovered in BALF samples ( Figure 4 ). These results indicated that the BALF sample might be more suitable for detecting MTB types and drug resistance by targeted capture sequencing, which are consistent with a previous study: Liu et al ( 2018 ) found BALF has significantly higher sensitivity (63.4%) than sputum (43.5%) for MTB detection by culture and nucleic acid amplification test; To et al ( 2018 ) discovered that the sensitivity and specificity of GeneXpert for TB diagnosis using BALF was 80 and 98% in sputum AFB smear negative patients, respectively. The main reason is that some patients were bacteriologically negative due to lack of sputum or false-negative due to poor sputum sample quality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, samples sequenced from BALF had a higher reference genome coverage as compared with those obtained from sputum, and this was correlated to the number of lineage-specific reads in BALF samples that was significantly more than in sputum samples, and the drug resistance was mostly discovered in BALF samples ( Figure 4 ). These results indicated that the BALF sample might be more suitable for detecting MTB types and drug resistance by targeted capture sequencing, which are consistent with a previous study: Liu et al ( 2018 ) found BALF has significantly higher sensitivity (63.4%) than sputum (43.5%) for MTB detection by culture and nucleic acid amplification test; To et al ( 2018 ) discovered that the sensitivity and specificity of GeneXpert for TB diagnosis using BALF was 80 and 98% in sputum AFB smear negative patients, respectively. The main reason is that some patients were bacteriologically negative due to lack of sputum or false-negative due to poor sputum sample quality.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, NGS directly from sputum can quickly generate a complete genetic drug resistance profile, faster than MGIT culture sequencing (Nimmo et al, 2017 ). Otherwise, BALF specimens have been applied widely in the detection of pulmonary pathogenic bacteria infection including MTB and NTM (Theron et al, 2013 ; Yamasaki et al, 2015 ; Liu et al, 2018 ). In our study, samples sequenced from BALF had a higher reference genome coverage as compared with those obtained from sputum, and this was correlated to the number of lineage-specific reads in BALF samples that was significantly more than in sputum samples, and the drug resistance was mostly discovered in BALF samples ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, about 50% and 15% patients bene ted from NAAT tests compared with smear and culture, respectively. NAAT test improved the positive detectable rate of PTB diagnosis as well as contributed to the effective anti-TB therapy by identifying species and drug susceptibility testing (12).…”
Section: Discussionmentioning
confidence: 99%
“…BALF is superior to the expectorated sputum in the diagnosis of lower respiratory tract tuberculosis [12,13]. Indeed in patients with suspected sputum-smear-negative pulmonary tuberculosis, Liu et., al, found that the sensitivity of 63.4% by culture or nucleic acid ampli cation test from BALF was higher than the sensitivity of 43.5% from sputum [13]. In addition, the presence of the Mycobacterium tuberculosis complex (MTBC) was detected in BALF specimen from patients who could no produce sputum.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adenosine deaminase activity in BALF is useful in the diagnosis of tuberculosis with negative sputum smears [14]. The authors found that, among all the collected samples, BALF samples positive for MTBC is associated with patients' characteristics including younger age, existence of pulmonary cavity and positive interferon-gamma release assay [13]. As suggested by studies on tuberculosis, the pathogens from various specimen sources may not only differ in susceptibility and speci city in smear or culture assay for diagnosis, but also re ect different risk factors for the host.…”
Section: Introductionmentioning
confidence: 99%